All-trans retinoic acids induce differentiation and sensitize a radioresistant breast cancer cells to chemotherapy. Issue 1 (December 2016) - Yan, Yunwen; Li, Zhen; Xu, Xiang; Chen, Clark; Wei, Wei; Fan, Ming; Chen, Xufeng; Li, Jian; Wang, Yuan; Huang, Jiaoti
Abstract Background Radiotherapy is of critical importance in the treatment of breast cancer. However, not all patients derive therapeutic benefit and some breast cancers are resistant to the treatment, and are thus evidenced with prospective distant metastatic spread and local recurrence. In this study, we investigated the potential therapeutic effects of all-trans retinoic acid (ATRA) on radiation-resistant breast cancer cells and the associated invasiveness. Methods The MCF7/C6 cells with gained radiation resistance after a long term treatment with fractionated ionizing radiation were derived from human breast cancer MCF7 cell line, and are enriched with cells expressing putative breast cancer stem cell biomarker CD44+ /CD24-/low /ALDH+ . The enhanced invasiveness and the acquired resistances to chemotherapeutic treatments of MCF7/C6 cells were measured, and potential effects of all-trans retinoic acid (ATRA) on the induction of differentiation, invasion and migration, and on the sensitivities to chemotherapies in MCF7/C6 cells were investigated. Results MCF7/C6 cells are with enrichment of cancer stem-cell like cells with positive staining of CD44+ /CD24-/low, OCT3/4 and NANOG. MCF7/C6 cells showed an increased tumoregensis potential and enhanced aggressiveness of invasion and migration. Treatment with ATRA induces the differentiation in MCF7/C6 cells, resulting in reduced invasiveness and migration, and increased sensitivity to Epirubincin treatment. Conclusion Our study suggests a potential clinic impact for ATRA as a chemotherapeutic agent for treatment of therapy-resistant breast cancer especially for the metastatic lesions. The study also provides a rationale for ATRA as a sensitizer of Epirubincin, a first-line treatment option for breast cancer patients.